17 The Impact of Transdermal Flunixin Meglumine on Biomarkers of Pain in Calves When Administered at the Time of Surgical Castration without Local Anesthesia. (10th April 2018) - Kleinhenz, M D; Van Engen, N; Smith, J; Gorden, P J; Wang, C; Perkins, S; Coetzee, J F
Abstract: Castration is a common husbandry practice performed on cattle in the United States and Canada. There are numerous reports supporting the use of non-steroidal anti-inflammatory drugs at the time of castration. The objective of this study was to determine the analgesic effects of transdermal flunixin when given at castration. Sixteen intact Holstein male calves were randomly assigned to the castrated group receiving flunixin (CAST-FLU; n = 8) or placebo castrated group (CAST-PLBO; n = 8). Seven steers served as the negative control (SHAM-PLBO) group for pain biomarkers. Flunixin treated calves received topical flunixin meglumine applied to their dorsal midline at the label dose of 3.33 mg/kg during the castration procedure while placebo calves received red-dyed propylene glycol. A surgical castration procedure was performed. Outcomes collected and analyzed included: plasma cortisol, substance P, ocular infrared thermography (IRT), prostaglandin E2, and gait analysis using a force plate (step force, foot contact area, foot contact pressure, impulse). Biomarkers were statistically analyzed using repeated measures with the calf being the repeated measure. There were significant treatment differences in plasma cortisol concentrations over time ( P = 0.0016) and the area under the effect curve tended to be different ( P = 0.0979). Specifically, there were significant differences in cortisol levels between the CAST-FLU and CAST-PLBO groups at 2, 3, 4, and 12 hours. There were no differences between treatment groups for substance P levels. Mean IRT values tended to be higher for CAST-FLU calves (35.4ºC) compared to CAST-PLBO (34.5ºC) and SHAM-PLBO (34.3ºC) calves ( P = 0.06). The total step force applied was similar for all treatment groups. The calves undergoing surgical castration placed more force onto their fore limbs ( P = 0.02) compared to the sham calves; indicating a shift in their weight distribution to the front limbs and away from the castration site. There were no measured differences in total step contact area and step contact pressure as part of the gait analysis. SHAM-PLBO calves has lower total impulses compared to CAST-FLU and CAST-PLBO ( P = 0.004). Transdermal flunixin had positive effects on cortisol concentrations and mitigation of the stress response for the first 12 hours. Transdermal flunixin provided negligible analgesic effects based on the pain biomarkers of substance P, IRT, and gait analysis when given at the time of castration. More work is needed to investigate transdermal flunixin as part of a multimodal analgesic plan that includes a local anesthetic.